PROFILE OF MEFENAMIC ACID AND DICLOFENAC SODIUM AS PAIN RELIEVER IN ORAL SURGERY AT DENTAL POLY - Muhammad Maulana Ma'sum (LPPM Universitas dr. Soebandi, 2024)
Pain is a physical disorder caused by tissue damage in the body that causes the body to feel uncomfortable when active. Pain medication may be medications that involve non-pharmacology and pharmacology using analgetics. An analgetic drug helps reduce pain, mainly through its workforce on the central nervous system, and changes a person's response to pain. The study employed an observational design with a quantitative descriptive research design. The population of this study is 1,367 data on the medical records of a patient-dental oral surgery patient in January 2022. The number of samples in the study was 94 data on medical records that had dental pain filled the inclusion crebe. The research is using a total sampling technique. Results have shown that the patients who take the highest levels of mefenamic acid drugs are 26- 45 years old (52.5%) and the patients who take the highest level of diclofenac sodium -45 (49%), followed by patients who take mefenamic acid and 69.1% at a rate of 62.5% and 69.1%, for the dose of the patient taking the mefenamic 2 x 500 mg (45%) and 3 x 500 mg (55%). This study concludes that patients who consume mefenamic acid and diclofenac sodium are aged 26-45 years with the most gender being female with the maximum dose being 3x500 mg for mefenamic acid and 3x50 mg for diclofenac sodium, the duration of which is the same-same 7 days.